An HPSG-based Shared-Grammar for the Chinese Languages: ZHONG [|] - Fan, Zhenzhen (2016)
This paper introduces our attempts to model the Chinese language using HPSG and MRS. Chinese refers to a family of various languages including Mandarin Chinese, Cantonese, Min, etc. These languages share a large amount of structure , though they may differ in orthogra-phy, lexicon, and syntax. To model these, we are building a family of grammars: ZHONG [ ]. This grammar contains in-stantiations of various Chinese languages, sharing descriptions where possible. Currently we have prototype grammars for Cantonese and Mandarin in both simplified and traditional script, all based on a common core. The grammars also have facilities for robust parsing, sentence generation , and unknown word handling.